OPTIMALISASI KEMAMPUAN BERBICARA DI DEPAN UMUM DI SMP NEGERI 11 PRABUMULIH - Puspa Indah Utami; Ratu Wardarita; Missriani Missriani; Dessy Wardiah; Yessi Fitriani; Siti Rukiyah; Muhammad Ali (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This service was carried out with the aim of developing the public speaking skills of teachers at SMP Negeri 11 Prabumulih. This ability is considered important so that the information conveyed by the teacher can be well received by the public. The methods applied in this training are lectures and discussions. this activity In the end, it can provide deeper knowledge and insight to the teachers of SMP Negeri 11 Prabumulih which can be used as provisions to build better communication interaction patterns in front of the audience.